ANALISIS PENGARUH AKREDITASI PROGRAM STUDI TERHADAP INTENSITAS BELAJAR DAN HARAPAN MASA DEPAN (Studi Kasus di Fakultas Sains dan Teknologi UIN Walisongo Semarang) - Eva Khoirun Nisa (Quality Assurance Institute (LPM) State Islamic University Walisongo Semarang, 2018)
The quality of a study program is assessed from the results of accreditation. Accreditation is also one of the requirements in applying for a job in a public or private institution. The hope is that the results of university accreditation will be satisfactory when students graduate from the college. With the Friedman test statistic, it can be seen the effect of the study program accreditation in the Faculty of Science and Technology on the learning intensity and future expectations in this study. It turned out that descriptively, the A study program's accreditation motivated students to study diligently and students really hoped to get a job or reputable college for further studies. In contrast, the students from study programs are accredited B, and C have medium and low learning intensity. Their hopes of getting a good job or place of further study are almost ordinary or almost nonexistent.